Hepcidin: a direct link between iron metabolism and immunity - Vyoral, Daniel; Petrák, Jirí (The international journal of biochemistry & cell biology, 2005)
Hepcidin, originally discovered in urine as a bactericidal peptide synthesized by hepatocytes was later proved to be a key regulator of iron metabolism at the whole body level, namely, in conditions of altered iron demand such as the increased or decreased total amount of body iron, inflammation, hypoxia and anemia. The major mechanism of hepcidin function seems to be the regulation of transmembrane iron transport. Hepcidin binds to its receptor, protein ferroportin, which serves as a transmembrane iron channel enabling iron efflux from cells. The hepcidin-ferroportin complex is then degraded in lysosomes and iron is locked inside the cells (mainly enterocytes, hepatocytes and macrophages). This leads to lowering of iron absorption in the intestine and to a decrease in serum iron concentration. Utilizing this mechanism, hepcidin regulates serum iron levels during inflammation, infection and possibly also in cancer. Under these conditions iron is shifted from circulation into cellular stores in hepatocytes and macrophages, making it less available for invading microorganisms and tumor cells. In anemia and hypoxia, hepcidin regulates the availability of iron for erythropoiesis. Hepcidin or hepcidin-related therapeutics could find a place in the treatment of various diseases such as hemochromatosis and anemia of chronic disease.
Keywords: Molecular Sequence Data; buněčná imunita; sekvence aminokyselin; Inflammation; kationické antimikrobiální peptidy; Hepcidins; mediátory zánětu; Iron Metabolism Disorders; zánět; železo; Immunity, Cellular; Inflammation Mediators; Iron; zvířata; Humans; Amino Acid Sequence; Antimicrobial Cationic Peptides; poruchy metabolismu železa; molekulární sekvence - údaje; lidé; hepcidiny; Animals